2013
DOI: 10.1177/0275074012469460
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing Expert Services by State Transportation Departments

Abstract: Privatization has increasingly become a policy option for government agencies struggling to meet rising demands for services but with fewer resources. In the transportation arena, many state departments of transportation (DOTs) have privatized by outsourcing highway functions to the private sector. But the outsourcing of technical and expert services such as those related to the design and construction of highway infrastructure may result in a smaller or less knowledgeable DOT workforce that is unable to perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…At times, outsourcing can lead to greater accountability, but contracting can pose risks to government agencies, as the contracting relationship throughout American history has had more than its share of blemishes (Durant, Girth, & Johnston, 2009; Keeney, 2007), and there are no a priori reasons to assume that outsourcing will produce cost savings or improved services. Empirical results have shown that outsourcing does not always lead to cost savings or improved service delivery (see, for example, Brudney, Fernandez, Ryu, & Wright, 2005; Condrey & Battaglio, 2007; Hodge, 2000; Yusuf & O’Connell, 2014), and may, under some circumstances, increase costs and/or lower quality (Bendick, 1989; Sclar, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…At times, outsourcing can lead to greater accountability, but contracting can pose risks to government agencies, as the contracting relationship throughout American history has had more than its share of blemishes (Durant, Girth, & Johnston, 2009; Keeney, 2007), and there are no a priori reasons to assume that outsourcing will produce cost savings or improved services. Empirical results have shown that outsourcing does not always lead to cost savings or improved service delivery (see, for example, Brudney, Fernandez, Ryu, & Wright, 2005; Condrey & Battaglio, 2007; Hodge, 2000; Yusuf & O’Connell, 2014), and may, under some circumstances, increase costs and/or lower quality (Bendick, 1989; Sclar, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the consequences of contracting out public services, a considerable amount of scholarly attention has been paid to the effects of service outsourcing on public sector employees, service performance, and governments’ cost savings (e.g., Buerger & Harris, 2021; Jang & Eger, 2019; Lee & Lee, 2020; Lee et al, 2019; Yusuf & O’Connell, 2014). First, scholars find that contracting out public services not only leads to increasing reliance on inexperienced, short-term, and less educated public employees but also negatively affects public employees’ working conditions, salaries, and job satisfaction (Fernandez et al, 2007; Rho, 2013; Vrangbæk et al, 2015; Yang & Kassekert, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to transaction cost economics, the limits to competition or contract failures (Crouch, 2015; Domberger & Jensen, 1997), it does not reduce costs or increase efficiency as expected. Furthermore, it does not automatically increase tax collection rates (e.g., Talit, 2012; Yusuf & O'Connell, 2014). Critics concerned about public policy and democracy maintain that outsourcing limits governmental control, leading to negative effects on employment, the fragmentation of the delivery of public services, the displacement of the traditional coordination between governmental arms, and the relegation of local policy makers to public service auditors and inspectors (Brown et al, 2006; Martin, 2010; Milward & Provan, 2000).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%